2018
DOI: 10.1108/jes-02-2017-0051
|View full text |Cite
|
Sign up to set email alerts
|

Brexit associated sharp depreciation and implications for UK’s inflation and balance of payments

Abstract: Purpose The purpose of this paper is to analyse the implications of exchange rate depreciation for inflation targeting and trade balance of UK in the context of the Brexit epoch. Design/methodology/approach The study employed a time-varying structural vector auto-regression (TVSVAR) model framework in which the sources of time variation were both the coefficients and variance-covariance matrix of the innovations on the data from January 1989 to September 2016. Findings The findings suggest that the depreci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Other researchers concluded that Brexit-induced policy uncertainty will continue to cause instability in key financial markets and has the potential to damage the real economy in both the UK and other European countries (Burdekin et al, 2017;Tielmann and Schiereck, 2017;Belke, 2017;Belke and Gros, 2017; Brexit and European stock markets Belke and Ptok, 2018;Padilla and Garrido, 2018). Other studies provided evidence on the effects on market volatility (Adesina, 2017;Sita, 2017;Cox and Griffith, 2018;Nishimura and Sun, 2018), exchange rate correlation (Alvarez-Diez, 2019) and the sharp depreciation of GBP (Ali Nasir and Simpson, 2018;Ali Nasir and Morgan, 2018), whereas Schiereck et al (2016) investigated the impact of Brexit on credit default swaps spread and EU banks' share prices and confirmed a negative impact on share prices and increased political uncertainty.…”
Section: Mf 467mentioning
confidence: 99%
“…Other researchers concluded that Brexit-induced policy uncertainty will continue to cause instability in key financial markets and has the potential to damage the real economy in both the UK and other European countries (Burdekin et al, 2017;Tielmann and Schiereck, 2017;Belke, 2017;Belke and Gros, 2017; Brexit and European stock markets Belke and Ptok, 2018;Padilla and Garrido, 2018). Other studies provided evidence on the effects on market volatility (Adesina, 2017;Sita, 2017;Cox and Griffith, 2018;Nishimura and Sun, 2018), exchange rate correlation (Alvarez-Diez, 2019) and the sharp depreciation of GBP (Ali Nasir and Simpson, 2018;Ali Nasir and Morgan, 2018), whereas Schiereck et al (2016) investigated the impact of Brexit on credit default swaps spread and EU banks' share prices and confirmed a negative impact on share prices and increased political uncertainty.…”
Section: Mf 467mentioning
confidence: 99%
“…For the adjustment of trade balance through appreciation and depreciation, one can go as far back as Hume's (1742) price–specie flow mechanism argument. The empirical studies since then often support a significant relationship between exchange rate and trade balance (Baharumshah, 2001; Bahmani‐Oskooee et al., 2019; Bahmani‐Oskooee & Ratha, 2004; Bahmani‐Oskooee & Saha, 2017; Nasir & Simpson, 2018; Stucka, 2004). However, the net benefit of depreciation (appreciation) can only be positive (negative) if the elasticities of export and import sum up to a value greater than unity, i.e., Marshall–Lerner condition (see Bahmani‐Oskooee et al, 2019; Bahmani‐Oskooee Ratha, 2004; Bahmani‐Oskooee & Saha, 2017; Devereux, 2000).…”
Section: Determinants Of the Trade Balancementioning
confidence: 99%
“…A separate study by Nasir and Simpson (2018) examined the consequences associated with the depreciation of the ER considering factors such as inflation on the trade balance of the UK between January 1989 and 2016 by employing a "time-varying" structural vector auto-regression model. The findings revealed that depreciation had a major impact on inflation along with the balance of trade in the UK.…”
Section: Literature Reviewmentioning
confidence: 99%